PENGEMBANGAN MEDIA AJAR MATERI GERAK PARABOLA BERBASIS GAME MENGGUNAKAN CONSTRUCT 2 UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS - Nur Iman, Haflan; Arjo, Sugianto (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
The purpose of our research is to produce physics learning media based on android games using the Construct 2 application to make it easier for students to understand learning and improve physics learning media. To find out the feasibility of E-learning learning media for Parabolic Motion material. and Development) ADDIE model, firstly conducts an analysis of problem analysis and needs analysis, the second makes story boards and media designs, the third tests material experts and media experts with experts in their respective fields, then conducts trials on For a small-scale trial held at Sman 6 Tangerang Regency with a total of 34 respondents, and a large-scale trial held at SMA Muhammadiyah 4 Tangerang City and Sman 6 Tangerang Regency with a total of 64 respondents, the data used by researchers through the observation method was analyzed qualitatively descriptively. if. Validation data were analyzed descriptively qualitatively and quantitatively. The average score for the small-scale test is 68.6% (good enough), and the large-scale test is 74.4 (good enough). So it can be interpreted that this application is suitable for use as a medium for learning physics.